Zur Begleitung Sterbender: Person- und systemorientierte Sterbebegleitung in pastoralpsychologischer Perspektive - Schmitt, Thomas (Tectum Verlag, 2023)
This book is primarily aimed at people who accompany the dying professionally or voluntarily, but also at other people who are in regular exchange through their work with elderly and dying people. Special attention is paid to the psychological as well as the religious and spiritual dimension of the human being. The focus is on accompaniment within a Christian horizon, but spirituality is understood here in a broad sense, so that this dimension can even come into play in the accompaniment of agnostics and atheists.